2023
DOI: 10.1101/2023.01.23.525149
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mis-spliced transcripts generatede novoproteins in TDP-43-related ALS/FTD

Abstract: Functional loss of TDP-43, an RNA-binding protein genetically and pathologically linked to ALS and FTD, leads to inclusion of cryptic exons in hundreds of transcripts during disease. Cryptic exons can promote degradation of affected transcripts, deleteriously altering cellular function through loss-of-function mechanisms. However, the possibility of de novo protein synthesis from cryptic exon transcripts has not been explored. Here, we show that mRNA transcripts harboring cryptic exons generate de novo protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
69
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 41 publications
(72 citation statements)
references
References 65 publications
3
69
0
Order By: Relevance
“…Excitingly, two new pre-print publications this year have independently reported the detection of cryptic peptides in the CSF of patients with ALS [57,58]. Irwin et al demonstrated that a newly characterised monoclonal antibody, specific to a TDP-43-dependent cryptic epitope encoded by the cryptic exon found in HDGFL2, detects the cryptic peptide in C9orf72-associated ALS.…”
Section: Opportunities For Novel Biomarkersmentioning
confidence: 99%
See 1 more Smart Citation
“…Excitingly, two new pre-print publications this year have independently reported the detection of cryptic peptides in the CSF of patients with ALS [57,58]. Irwin et al demonstrated that a newly characterised monoclonal antibody, specific to a TDP-43-dependent cryptic epitope encoded by the cryptic exon found in HDGFL2, detects the cryptic peptide in C9orf72-associated ALS.…”
Section: Opportunities For Novel Biomarkersmentioning
confidence: 99%
“…Strikingly, this includes pre-symptomatic mutation carriers [57]. In Seddighi et al, our groups first demonstrated the presence of de novo cryptic peptides in iPSC-derived neurons with TDP-43 knockdown, and then used a novel targeted proteomics assay to confirm the presence of cryptic peptides in CSF of patients with ALS-FTD [58]. Further work will be needed to assess the specificity and sensitivity of cryptic peptides as biomarkers, but, taken together, these discoveries are encouraging steps towards facilitating earlier diagnosis of ALS, and also providing a way of measuring target engagement in clinical trials for new therapies aimed at restoring TDP-43 function.…”
Section: Opportunities For Novel Biomarkersmentioning
confidence: 99%
“…Additionally, cryptic exon-containing transcripts can potentially be translated into novel proteins, which may affect cell fitness and produce neo-antigens in tumors. [64][65][66] These findings shine light on the role of hnRNPM not only as a repressor of alternatively spliced and cryptic exon inclusion, but also a guardian of transcriptome stability and proteome integrity.…”
Section: Discussionmentioning
confidence: 99%
“…Diagnostic approaches include testing DEU changes or cryptic exon emergence with PCR or RNA-sequencing of biofluids (57, 88). Another emerging approach is designing aptamers or antibodies to cryptic peptides or neoepitopes that result from DEU events (89, 90). Indeed, the isoform switch of POLDIP3 from variant-1 to variant-2 due to exon skipping in POLDIP3 has also been proposed to be a measurable protein biomarker due to variant-2 being rarely detected in normal tissues (55).…”
Section: Discussionmentioning
confidence: 99%